2009
DOI: 10.1074/jbc.m900020200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for SHP2 in Promoting HER2-induced Signaling and Transformation

Abstract: The Src homology phosphotyrosyl phosphatase 2 (SHP2) plays a positive role in HER2-induced signaling and transformation, but its mechanism of action is poorly understood. Given the significance of HER2 in breast cancer, defining a mechanism for SHP2 in the HER2 signaling pathway is of paramount importance. In the current report we show that SHP2 positively modulates the Ras-extracellular signal-regulated kinase 1 and 2 and the phospoinositide-3-kinase-Akt pathways downstream of HER2 by increasing the half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(124 citation statements)
references
References 47 publications
7
114
1
2
Order By: Relevance
“…In cells depleted of PKCδ (shδ193 and shδ203), ligand-induced autophosphorylation of ErbB2 Y1221/1222 and Y1248 was slightly reduced, while phosphorylation of ErbB2 at Y877 was more dramatically reduced (Figure 4A and 4B, graphs) (40). Of note, total ErbB2 receptor protein was decreased in the absence of ErbB2 dimerization in shSCR cells, consistent with the findings that ErbB2 activation can decrease receptor turnover and stability (4143). …”
Section: Resultssupporting
confidence: 86%
“…In cells depleted of PKCδ (shδ193 and shδ203), ligand-induced autophosphorylation of ErbB2 Y1221/1222 and Y1248 was slightly reduced, while phosphorylation of ErbB2 at Y877 was more dramatically reduced (Figure 4A and 4B, graphs) (40). Of note, total ErbB2 receptor protein was decreased in the absence of ErbB2 dimerization in shSCR cells, consistent with the findings that ErbB2 activation can decrease receptor turnover and stability (4143). …”
Section: Resultssupporting
confidence: 86%
“…Genetic and biochemical studies in recent years have suggested that SHP2 plays a broad role not only in cell proliferation [12], survival [13], and differentiation [14], but also in development [15,16] and tumorigenesis [17][18][19] of malignancies via Ras/Erk [20], PI3K/Akt [21] and other signaling pathways. In accordance to a recent study [18], our previous studies [22][23][24] have demonstrated that SHP2 plays a crucial role in breast oncogenesis. Recently, we have also found for the first time that SHP2 is widely expressed by lung cancer cells, and that the high expression of SHP2 may promote the invasion and metastasis of NSCLC through angiogenesis and the lymphatic system [25,26].…”
Section: Introductionsupporting
confidence: 90%
“…S4D), suggesting that EGFRvIII and c-MET are substrates of SHP2. These specific interactions have not been reported previously, but it has been reported that SHP2 can directly dephosphorylate other receptors, including HER2 (Zhou and Agazie, 2009), based on experiments using SHP2 DM .…”
Section: Shp2 Negatively Regulates Phosphorylation Of Egfrviii and C-metmentioning
confidence: 67%